Prominent Murder Victims of the Pre- and Early Islamic Periods Including the Names of Murdered Poets : Introduced, Edited, Translated from the Arabic, and Annotated - Ḥabīb, Muḥammad ibn (Handbook of Oriental Studies. Section 1 The Near and Middle East, 2021)
Muḥammad ibn Ḥabīb (d. 860), a specialist in Arab history, tribal genealogy, and poetry, who lived in Baghdad, collected in his Prominent Murder Victims many stories of murderers and murder victims from the legendary pre-Islamic past, such as how Bilqīs, the Arabic name for the Queen of Sheba, came to power, to the assassinations ordered by viziers or caliphs in the early Islamic centuries. A lengthy appendix deals with poets from pre- and early Islamic times who were killed. The stories are entertaining as well as informative. Strikingly, the author refrains from explicit moralising. The present book offers a richly annotated English translation together with an improved Arabic text and indexes of persons, places, and rhymes.